Dampak Upah Minimum, Produk Domestik Regional Bruto, Inflasi dan Tingkat Pendidikan terhadap Penyerapan Tenaga Kerja di Provinsi Jawa Timur Tahun 2011-2020 - Maksum Maksum; Khovifa Lindarsi Farawangsa Khovifa (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
The population growth in Indonesia is getting faster and faster as well as the population growth in East Java Province. The total population of East Java Province is the second largest in Indonesia after West Java Province. Data on the population growth rate of East Java Province in percentage from 2010 to 2020 reached 0.79%. However, the large rate of population growth in East Java Province has not been matched by a large number of labor absorbed in various economic sectors. This research is aimed to analyze the factors influencing minimum wage, gross regional domestic product, inflation, and education level on labor absorption in East Java from 2011-2020 in the period of 10 years. This research is used quantitative research with a descriptive method. The decision-making sample in this research used purposive sampling, it got 7 regencies/cities for this research sample. The source of data is taken generally from the Central Bureau of Statistics (BPS). This study used the panel data regression analytical method of secondary data and the data selected for the fixed effect model, the software used in this research is Eviews 9. The result showed as a simultaneous test, it is found that minimum wage, gross regional domestic product, inflation, and education level have a significant effect on labor absorption. As a partial test minimum wage and inflation have no significant effect on labor absorption, but gross regional domestic product and the education level variable has a significant effect on labor absorption. The value of coefficient determination (R2) in this research in the amount of 99,86% can be concluded on the dependent variable labor absorption. Meanwhile, 0,14% can be concluded by another variable.